Teachers as Agents of Value and Social Character at Bina Bintang Inclusive Preschool: A Case Study of PT Arutmin Indonesia NPLCT, South Kalimantan - Nadya Izana, Nyimas; Putra, Dimas Indrayanto; Muhana, Muriyana (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2026)
This study examines how teachers serve as agents of socialization in shaping children’s social character, specifically within the inclusive education setting at Bina Bintang Kindergarten, which is managed by PT Arutmin Indonesia NPLCT in Kotabaru Regency, South Kalimantan. The research targets mechanisms, such as exemplary behavior, classroom norms, and conflict mediation as pathways for internalizing social values among children with special needs. Employing a qualitative case study approach, the study collects data through participant observation, in-depth interviews with teachers, the principal, and homeroom teachers, as well as documentation of classroom activities. Research findings indicate that teachers serve as role models in instilling values such as empathy, mutual aid, fairness, and respect for diversity. The consistent enforcement of classroom rules such as taking turns speaking, sharing play materials, and resolving conflicts nonviolently contributes to the development of self-discipline and an understanding of social boundaries among children with special needs. Conflict mediation through dialogue serves as an effective social learning space that helps children recognize emotions, understand others’ perspectives, and develop collaborative solutions. These practices strengthen a classroom culture that is safe, supportive, and inclusive. The implications of this research underscore the importance of designing structured social routines, strengthening collaboration among special education teachers, homeroom teachers, and school principals, and developing internal guidelines for social-emotional learning within the school. Through a planned and sustained approach, education at Bina Bintang Inclusive Preschool can serve as a strategic foundation for developing children’s social character from an early age, particularly for children with special needs.